A comparison of Bartonella henselae infection in immunocompetent and immunocompromised mice. - Rebekah L Bullard; Mercedes Cheslock; Shiva Kumar Goud Gadila; Ricardo G Maggi; Edward B Breitschwerdt; Ahmad A Saied; Monica E Embers (PLoS ONE)
Bartonellosis refers to disease caused by the Bartonella genus of bacteria. The breadth of disease manifestations associated with Bartonella is currently expanding and includes regional lymphadenopathy, rheumatic, ocular, and neurological disorders. The dearth of knowledge regarding diagnosis, treatment and pathogenesis of this disease can be partially attributed to the lack of a reliable small animal model for the disease. For this study, Bartonella henselae, the most common species associated with human disease, was injected into Swiss Webster (SW) mice. When the outcome indicated that productive infection did not occur, SCID/Beige (immune compromised) mice were inoculated. While SW mice may potentially harbor an acute infection, less than 10 days in length, the SCID/Beige model provided a sustained infection lasting up to 30-days. These data indicate that SCID/Beige mice can provide a model to study Bartonella infection, therapeutics, and vector dynamics in the future.